Galleria mellonella como modelo invertebrado hospedeiro de infecção para estudo do complexo Candida guilliermondii: análise de virulência - Luiz, Rita Angelica [UNIFESP] (2018)
The genus Candida is responsible for most of fungal infections in the hospital environment. Although C. albicans remains the most prevalent species in candidemia, there is an increase in infections by non-Candida albicans species, and among them, there are some species caused by the C. guilliermondii complex. Although the pathogenic potential of C. guilliermondii has already been demonstrated, there are few studies in the literature evaluating the mechanisms of virulence involved during the development of the infection by this complex. OBJECTIVES: To evaluate putative differences in the virulence of isolates representative of the two clinical relevance species belonging to the C. guilliermondii complex (C. guilliermondii sensu stricto and C. fermentati) through analysis of biofilm formation and survival curve in the Galleria mellonella infection model. MATERIALS AND METHODS: A total of 61 isolates of the C. guilliermondii complex obtained from blood cultures of patients with documented fungus in Latin American hospitals from 2008-2016 were selected from the Bank of Microorganisms of Laboratório (LEMI), at the Federal University of São Paulo (UNIFESP). Isolates from this complex were previously identified by Molecular Sequencing method using the ITS region. The biofilm formation assays were performed on a microtiter plate and quantified by staining with crystal violet. Infection in the G. mellonella model was performed using inoculum of six representative isolates of each C. guilliermondii complex species, and the survival curve of the invertebrates was evaluated. RESULTS: Among the 61 isolates of the C. guilliermondii complex, 39 were identified and confirmed as C. guilliermondii (sensu stricto) and 22 as C. fermentati. Regarding biofilm formation by C. guilliermondii (sensu stricto) isolates, 12 (30.8%) were classified as low formers, 20 (51.3%) intermediate and seven (17.9%) as high biofilm formers. For C. fermentati, 4 isolates (16.7%) presented low biofilm formation, 12 (50%) and 8 isolates (33.3%) presented intermediate and high capacity, respectively. In a model of infection using G. mellonella, it was observed that both species were able to trigger an infectious process in the invertebrate host, and no relationship between mortality curve of the animals and the greater or lesser biofilm production by the tested isolates was documented. CONCLUSIONS: The present work demonstrated that species of C. fermentati and C. guilliermondii sensu stricto present similar characteristics of pathogenicity, at least in relation to biofilm production and death curve in invertebrate models.